Enhancement of the stability of chlorophyll using chlorophyll-encapsulated polycaprolactone microparticles based on droplet microfluidics. (15th February 2020) - Hsiao, Ching-Ju; Lin, Jui-Fen; Wen, Hsin-Yi; Lin, Yu-Mei; Yang, Chih-Hui; Huang, Keng-Shiang; Shaw, Jei-Fu
Highlights: Improving chlorophyll stability for application in the food industry. The article proposed a polymer coating method through droplet microfluidics. This coating method was use a PCL to prolong the stability of chlorophyll. Abstract: Chlorophyll is a valuable bioactive compound, which is used as a natural food coloring agent and a photosensitizer for photodynamic therapy because of its antioxidant properties, antimutagenic ability, and near-infrared fluorescence. However, chlorophyll is unstable when it comes to retaining its antioxidant activity, when exposed to oxygen, high temperature, or light environments. To enhance the stability of chlorophyll, a polymer encapsulation method was proposed. Polycaprolactone (PCL) was employed to encapsulate the chlorophyll, and the particles size of the composites was controlled through droplet microfluidics. The composites (chlorophyll-encapsulated PCL particles) were characterized through UV–VIS spectrometry, SEM, optical microscopy, and light exposure. The particles were spherical, with diameters adjustable from 68 to 247 μm. Additionally, the chlorophyll-encapsulated PCL particles exhibited considerably prolonged chlorophyll stability. The solid microparticle is more convenient for storage and transportation, and have great potential for application in the food industry.